International emissions trading in a noncooperative climate policy game - Bjart Holtsmark; Dag Einar Sommervoll (Statistics Norway, Research Department, 2012)
Using a non cooperative climate policy game applied in the literature, we find that an agreement with international emissions trading leads to increased emissions and reduced efficiency.
Keywords: C7; Q2; Q4; 330; Climate change; international environmental agreements; emissions trading; non-cooperative game theory.